V2O5 Cryogel: A Versatile Electrode for All Solid State Lithium Batteries. Issue 16 (22nd November 2019) - Maroni, Fabio; Bruni, P.; Suzuki, N.; Aihara, Y.; Agostini, M.; Branchi, M.; Navarra, M. A.; Nobili, F.; Matic, A.; Croce, F.
Abstract : All solid-state lithium batteries (ASLB) are paving the attention of the battery community due to the possibility of improving safety at good energy level. Their future development requires the investigation of new electrodes chemistries both based on intercalation or conversion mechanism. In this work we report on the synthesis and characterization of a V2 O5 cryogel electrode and its application in ASLB. The combination of V2 O5 cryogel and a solid-state electrolyte shows appealing properties of high capacity and enhanced safety.